由“不等式(2a-b)x+3a-4b<0的解为x>九分之四”可以知道2a-b<0
∴(2a-b)x<4b-3a,(b-2a)x>3a-4b,x>(3a-4b)/(b-2a)
∴(3a-4b)/(b-2a)=4/9,不妨使3a-4b=4,b-2a=9
解得a=-8,b=-7
代入(a-4b)x+2a-3b>0,得20x+5>0
∴其解为x>-1/4
或:
(2a-b)x+3a-4b<0
(2a-b)x<4b-3a
x>(4b-3a)/(2a-b) (当2a-b<0时)
而x>4/9
所以,(4b-3a)/(2a-b)=4/9
36b-27a=8a-4b
40b=35a
b=35a/40=7a/8
2a-b=2a-7a/8=9a/8<0
所以,a<0,b<0
a-4b=a-4*7a/8=a-28a/8=-5a/2>0
(a-4b)x+2a-3b>0
(a-4b)x>3b-2a
x>(3b-2a)/(a-4b)=(3*7a/8-2a)/(a-4*7a/8)
=(5a/8) / (-20a/8)
=-5/20
=-1/4
由已知知,2a-b>0;且(4b-2a)/(2a-b)=4/9;推出b>0;a=8b/7;带入后式得
x<-5/24